(untitled) (LINGUISTICA, 2015)
This study deals with the use of sexist language in Dagelanaccount on Instagram. The objectives of this study were to find out the dominat type of ambivalent sexsim and the most prominent gender discussed in Dagelanaccount. This study was conducted by using descriptive qualitative method. The data were collected from Dagelanaccount in Instagramby capturing some pictures that have captions related to sexist language and then analyzed into two types of ambivalent sexism theory, hostile sexism and benevolent sexism. The result showed that there were 24 sentences related to hostile sexism and 26 sentences related to benevolent sexism. The using of benevolent sexism is the most dominant used in Dagelanaccount and the most prominent gender discussed in Dagelanaccount is female in hostile sexism.